Horichia dressleri. A new genus recorded for Costa Rica and a truly rare orchid? - Pupulin, Franco (2017)
Orchid collectors, as well as scientists, know that some species are rarer than others. “Know” should perhaps be used in this context with some caution as, in general, rarity is something closer to a perception than to a specific category of frequency, assessed on the basis of available data. The categorization of an orchid species as “rare” is frequently just the result of its low appearance in cultivation, and that scarcity is often assumed to be a reflection of true rarity in nature as well; but that is not always the case.